Population Characteristics of Molluscs of the Family Sphaeriidae (Mollusca, Bivalvia) of Reservoirs and Watercourses in the Northern Right-Bank Polissia of Ukraine (Pripyat Sub-Basin) - L. M. Shevchuk; L. V. Bylyna (Zoodiversity, 2025)
A total of 18 species of molluscs of the family Sphaeriidae (Mollusca, Bivalvia) were found in the water bodies of the northern right-bank Polissia of Ukraine (Pripyat sub-basin). Sphaerium solidum is indicated for the Pripyat sub-basin for the first time. The largest number of species (12) was found in the Horyn River, nine in the Pripyat River, six in the Uzh and Sluch Rivers, three in the Khomora River, two in the Ubort River and no species in the Turiya River. A total of 12 species were found in small rivers and six species in streams. Sphaeriidae molluscs were not found at all in out-of-channel ponds. In one collection point, from one to eight species were recorded at the same time. S. solidum, S. nucleus, and S. rivicola had the highest rates of occurrence in the study region (up to 15 %), for the rest of the species this rate was 1–10 %. The total incidence of Sphaeriidae was 44 %. The highest density of S. nucleus was recorded in the Uzh (29 specimens/m2), in most of the sampling sites the value did not exceed 10, mostly 1–3 specimens/m2. The lists of species (according to Sørensen's index) were most similar for the rivers Styr and Horyn (59 %), Pripyat and Horyn (57 %), Styr and Uzh (55 %), Ubort and Uzh (50 %). Changing conditions in anthropogenically modified water landscapes are probably the main reason for the disappearance of representatives of the family, which is why it is necessary to analyse the ecological characteristics of Sphaeriidae habitats.